2014
DOI: 10.2967/jnumed.113.122895
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment and Dosimetry of 2 Novel PDE10A PET Radiotracers in Humans: 18F-MNI-659 and 18F-MNI-654

Abstract: Phosphodiesterase (PDE) 10A is an enzyme involved in the regulation of cyclic adenosine monophosphate and cyclic guanosine monophosphate and is highly expressed in medium-sized spiny neurons of the striatum, making it an attractive target for novel therapies for a variety of neurologic and psychiatric disorders that involve striatal function. Potential ligands for PET imaging of PDE10A have been reported. Here, we report the first-in-human characterization of 2 new PDE10A radioligands, 2-(2-(3-(1-(2-fluoroethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…The TACs of the cerebellum were better described by the 2TCM than the 1TCM, similarly as has been described for several other PDE10A radioligands [10, 11, 14, 16, 18]. Possible explanations for this include a small fraction of specific binding, a kinetically distinguishable nondisplaceable compartment, tissue heterogeneity (gray and white matter), or a contamination from BBB-penetrating radiometabolites [38, 39].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The TACs of the cerebellum were better described by the 2TCM than the 1TCM, similarly as has been described for several other PDE10A radioligands [10, 11, 14, 16, 18]. Possible explanations for this include a small fraction of specific binding, a kinetically distinguishable nondisplaceable compartment, tissue heterogeneity (gray and white matter), or a contamination from BBB-penetrating radiometabolites [38, 39].…”
Section: Discussionsupporting
confidence: 55%
“…It is noted that the majority of the studies of PDE10A radioligands did not in detail evaluate the influence of radiometabolites on quantification. For example, only studies using [ 18 F]JNJ-42259152 [16] or [ 18 F]MNI-659 [18] have examined the effect of PET measurement duration on the quantification, and for both radioligands an increase in V T value was obtained with increasing PET measurement duration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several potent radiotracers targeting PDE10A have been developed and validated in vivo by different groups (Barret et al, 2014; Barret, 2012; Celen et al, 2010; Celen et al, 2013; Harada et al, 2015; Hwang et al, 2014; Kehler et al, 2014; Van Laere et al, 2013a; Van Laere et al, 2013b), including another radiolabeled MP-10 analogue, [ 18 F]JNJ42259152. However, as found with MP-10, the possible influence of a brain-penetrating radioactive metabolite of [ 18 F]JNJ42259152 was reported (Celen et al, 2013; Van Laere et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…(2-(2-(3-(4-(2-[ 18 F]fluoroethoxy)phenyl)- 7-methyl-4-oxo-3,4-dihydroquinazolin-2-yl)ethyl)-4- isopropoxyisoindoline-1,3-dione) ([ 18 F]MNI-659) is a PET biomarker with specificity for PDE10 [16]. PET studies in early HD patients have demonstrated significantly reduced striatal [ 18 F]MNI-659 compared to healthy controls [17, 18].…”
Section: Reviewmentioning
confidence: 99%